A rare case of giant hepatic angiomyolipoma with subcapsular rupture - Wu, Cuiting; Yang, Yang; Tian, Feng; Xu, Yuan; Qu, Qiang (Frontiers in Surgery, 2023)
Hepatic angiomyolipoma (HAML) is a rare mesenchymal neoplasm that predominantly affects middle-aged women. In this study, we present a case of a 49-year-old woman with a giant HAML accompanied by spontaneous subcapsular rupture. The patient initially experienced nausea and abdominal distention, followed by an enlargement of the upper abdominal circumference. Laboratory examination revealed decreased serum hemoglobin, while tumor biomarkers were within normal ranges. Imaging studies, such as abdominal ultrasound and contrast-enhanced computed tomography (CT), demonstrated a large upper abdominal mass with heterogeneous density and hypervascularity. The tumor appeared to have invaded the left liver, raising concerns about possible malignancy. Subsequent positron-emission tomography/CT confirmed increased fluorodeoxyglucose uptake in the mass. Laparoscopic exploration revealed a protruding, well-encapsulated tumor from the left liver, exhibiting subcapsular hemorrhage. Surgical resection of the tumor and the left liver was performed, leading to a successful outcome.